Dissolvable solid structure having a first layer and a second layer

By designing the composition of the first and second layers in the dissolved solid structure, using high melting point fat materials and cationic surfactants, the shortcomings of structural strength and cutting convenience in the prior art are solved, and higher flexibility and performance improvements are achieved.

JP2025509413AActive Publication Date: 2025-04-11PROCTER & GAMBLE CO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024553804
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-10
Filing Date
2023-03-10
Publication Date
2025-04-11
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing dissolved solid structures have shortcomings in maintaining structural strength and ease of cutting, and are difficult to be compatible with components of different levels, affecting their performance and convenience of use.

Method used

The solubilized solid structure consisting of a first layer and a second layer, wherein the first layer contains 20% to 100% water-soluble polymer and the second layer contains 1% to 50% high melting point fat material and cationic surfactant, thereby increasing the flexibility and strength of the combination through this hierarchy.

Benefits of technology

The performance of reducing polymer content while maintaining structural strength, improving combination flexibility and ease of cutting, while allowing compatibility with incompatible components at different levels, enhancing overall performance and aesthetic features.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509413000001_ABST
    Figure 2025509413000001_ABST
Patent Text Reader

Abstract

The present invention relates to a dissolvable solid structure comprising: (a) a first layer, the first layer comprising, by weight of the first layer, 20% to 100% of a first water-soluble polymer by weight of the first layer; and (b) a second layer comprising, by weight of the first layer, 1% to 50% of a second water-soluble polymer by weight of the second layer, a high melting point fatty material having a carbon chain length of C12 to C22 or a mixture thereof, the melting point being above 25° C., and a cationic surfactant. The present invention provides, for example, improved flexibility and solubility in compositions while maintaining sufficient structural integrity during manufacture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dissolvable solid structure comprising: (a) a first layer, the first layer comprising, by weight of the first layer, about 20% to about 100% of a first water-soluble polymer by weight of the first layer; and (b) a second layer, the second layer comprising, by weight of the first layer, about 1% to about 50% of a second water-soluble polymer by weight of the second layer, a high melting point fatty substance having a carbon chain length of C12 to C22 or a mixture thereof, the melting point being above 25° C., and a cationic surfactant. The present invention provides, for example, improved flexibility in the composition while maintaining a certain structural strength during manufacturing. [Background technology]

[0002] Many personal care products and other consumer products available on the market today are sold in liquid form. Although liquid products are widely used, they often involve trade-offs in terms of packaging, storage, transportation, and convenience of use. Liquid consumer products are typically sold in bottles, which increases costs and packaging waste, much of which ends up in landfills.

[0003] Hair care products in the form of dissolvable solid structures offer an attractive format for consumers. Executions of dissolvable solid structures can include dissolvable films, compressed powders in solids, fibrous structures, porous foams, dissolvable deformable solids, powders, and the like. Summary of the Invention [Problem to be solved by the invention]

[0004] However, there remains a need for such dissolvable solid structures that deliver at least one of the following: The flexibility of the composition is improved, in particular allowing the polymer content to be reduced in at least one of the layers while maintaining a certain structural strength during manufacture and ease of cutting during and after manufacture. A layer can incorporate a component that is incompatible with at least one of the components in another layer. Allows for improved bonding of particles in articles Improved aesthetic features selected from the group consisting of printing, embossing, texturing, coloring, and combinations thereof. [Means for solving the problem]

[0005] The present invention provides a dissolvable solid structure comprising: a. a first layer, the first layer comprising, by weight of the first layer, about 20% to about 100% of a first water-soluble polymer; b. A dissolvable solid structure comprising a second layer comprising: about 1% to about 50% by weight of the second layer of a second water-soluble polymer; a high melting point fatty substance having a carbon chain length of C12 to C22 or a mixture thereof, the high melting point fatty substance having a melting point above 25°C; and a cationic surfactant. [Brief description of the drawings]

[0006] [Figure 1] FIG. 2 is a schematic diagram of an example of a process for making a fiber element of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of an example die used in the process of FIG. 1 at an enlarged scale. [Diagram 3] FIG. 1 is a schematic diagram of an example process for making an example fibrous structure according to the present disclosure. [Figure 4] FIG. 4 is a schematic diagram of an example die used in the process of FIG. 3 at an enlarged scale. [Diagram 5] FIG. 2 is a schematic diagram of a cross section of another example fibrous structure according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] definition As used herein, the dissolvable solid structure may be referred to herein as a "dissolvable solid structure," a "structure," or a "dissolvable structure."

[0008] As used herein, "soluble" means that the dissolvable solid structure dissolves completely in water or provides a uniform dispersion when mixed in water according to the hand dissolution test. The dissolvable solid structure has a hand dissolution value of about 1 to about 30 strokes, alternatively about 2 to about 25 strokes, alternatively about 3 to about 20 strokes, or alternatively about 4 to about 15 strokes, as measured by the hand dissolution method.

[0009] As used herein, "flexible" means that the dissolvable solid structure meets the distances up to the maximum force values ​​discussed herein.

[0010] "Fiber structure" as used herein means a structure comprising one or more fiber elements and optionally one or more particles. A fibrous structure as described herein can refer to an association of fiber elements and optionally particles that together form a structure, such as a unitary structure, that can perform a function.

[0011] The fibrous structures of the present invention may have multi-ply fibrous structures that include two or more different fibrous structure plies, each of which may be the same or different from the other plies.

[0012] A layer containing fibrous elements may be referred to as a ply. A ply may be a fibrous structure that may be homogenous or layered, as described herein.

[0013] A single-ply fibrous structure, or a multi-ply fibrous structure comprising one or more fibrous structure plies as described herein, has a basis weight of 5000 g / m2 or more when measured in accordance with the basis weight test method described herein. 2For example, a single-ply or multi-ply fibrous structure according to the present invention may have a basis weight of less than 10 g / m2, as measured according to the basis weight test method. 2 Super~approx. 5000g / m 2 , and / or 10 g / m 2 Super ~ about 3000g / m 2 , and / or 10 g / m 2 Super ~ about 2000g / m 2 , and / or 10 g / m 2 Super ~ about 1000g / m 2 , and / or 20 g / m 2 Super ~ about 800g / m 2 , and / or 30 g / m 2 Super ~ about 600g / m 2 , and / or 50 g / m 2 Super~approx. 500g / m 2 , and / or 300 g / m 2 Super ~ about 3000g / m 2 , and / or 500 g / m 2 Super ~ about 2000g / m 2 The basis weight may be indicated as:

[0014] In one embodiment, the fibrous structure of the present invention is a "monolithic fibrous structure."

[0015] "Unitary fibrous structure," as used herein, is an arrangement comprising two or more and / or three or more multiple fibrous elements that are intertwined or otherwise associated with one another to form a fibrous structure and / or fibrous structure ply. The unitary fibrous structure of the present invention may be one or more plies within a multi-ply fibrous structure. In one embodiment, the unitary fibrous structure of the present invention may comprise three or more different fibrous elements. In another embodiment, the unitary fibrous structure of the present invention may comprise two or more different fibrous elements.

[0016] As used herein, "article" refers to a consumer use unit, consumer unitary dose unit, consumer use saleable unit, single dose unit, or other form of use that includes a monolithic fiber dissolving solid structure and / or includes one or more fiber structures of the present invention.

[0017] "Fiber element," as used herein, means an elongated particle having a length significantly greater than its average diameter, i.e., a ratio of length to average diameter of at least about 10. A fiber element can be a filament or a fiber. In one embodiment, a fiber element is a single fiber element, rather than a yarn that includes multiple fiber elements.

[0018] The fiber elements of the present invention may be spun from a filament-forming composition, also referred to as a fiber element-forming composition, via a suitable spinning process operation such as meltblowing, spunbonding, electrospinning, and / or rotary spinning.

[0019] The fibrous elements of the present invention may be monocomponent (a single integral solid piece rather than two distinct parts such as core / sheath bicomponent) and / or multicomponent. For example, the fibrous elements may comprise bicomponent fibers and / or filaments. The bicomponent fibers and / or filaments may be in any form, such as side-by-side, sheath-core, islands-in-the-sea, etc.

[0020] "Filament" as used herein means an elongated particle as described above exhibiting a length of 2 inches or more, and / or 3 inches or more, and / or 4 inches or more, and / or 6 inches or more. Filaments are typically considered to be essentially continuous or substantially continuous. Filaments are relatively longer than fibers. Non-limiting examples of filaments include meltblown filaments and / or spunbond filaments.

[0021] "Fiber" as used herein means an elongated particle as described above exhibiting a length of less than 2 inches and / or less than 1.5 inches and / or less than 1 inch. Fibers are typically considered to be discontinuous in nature. Non-limiting examples of fibers include staple fibers produced by spinning filaments or filament tows and then cutting the filaments or filament tows into pieces less than 2 inches to produce fibers. Thus, references herein to filaments include fibers made from such filaments unless otherwise specified. Fibers are typically considered to be discontinuous in nature as opposed to filaments which are considered to be essentially continuous.

[0022] "Filament-forming composition" and / or "fiber element-forming composition" as used herein means a composition suitable for making fiber elements of the present invention, such as by meltblowing and / or spunbonding processes. The filament-forming composition includes one or more filament-forming materials that exhibit properties that make the material suitable for spinning into fiber elements. In one embodiment, the filament-forming material includes a polymer. In addition to the one or more filament-forming materials, the filament-forming composition may include one or more additives, such as one or more active agents. Additionally, the filament-forming composition may include one or more polar solvents, such as water, in which one or more, such as all of the filament-forming materials and / or one or more, such as all of the active agents, are dissolved and / or dispersed prior to spinning fiber elements, such as filaments, derived from the filament-forming composition.

[0023] As used herein, "porous" means that the dissolvable solid structure has spaces, voids, or gaps (commonly referred to herein as "pores") caused by a microscopic, complex, three-dimensional organization that provide channels, pathways, or passageways through which liquids can flow.

[0024] As used herein, "porosity" and "percent porosity" are used interchangeably and each refer to a measure of the void volume of a dissolvable solid structure; [1-([basis weight of soluble solid structure] / [thickness of soluble solid structure x density of dry material of chunk])] x 100% is calculated as The units are adjusted so that they are reduced and multiplied by 100% to provide the percent porosity.

[0025] The dissolvable solid structure may be referred to herein as a "dissolvable solid structure" or a "dissolvable structure."

[0026] The terms "molecular weight" or "molecular weight" refer to weight average molecular weight, unless otherwise specified. Molecular weight is measured using gel permeation chromatography (GPC), an industry standard method.

[0027] As used herein, articles such as "a" and "an," when used in a claim, are understood to mean one or more of what is claimed or described.

[0028] As used herein, the terms "include," "includes," and "including" are meant to be open-ended.

[0029] The methods disclosed in the Test Methods section of this application should be used to determine the values ​​of each of the parameters of Applicants' invention, including those discussed in the Dissolvable Structures - Physical Properties section below.

[0030] All percentages and ratios are calculated by weight unless otherwise specified. All percentages and ratios are calculated based on the total composition unless otherwise specified.

[0031] It should be understood that every maximum numerical limitation given throughout this specification includes every lower numerical limitation, as if such lower numerical limitations were expressly written herein. Every minimum numerical limitation given throughout this specification includes every higher numerical limitation, as if such higher numerical limitations were expressly written herein. Every numerical range given throughout this specification includes every narrower numerical range that falls within such broader numerical range, as if such narrower numerical ranges were all expressly written herein.

[0032] Dissolvable solid structure (dissolvable solid article) The dissolvable solid structure of the present invention comprises a first layer containing a first water-soluble polymer and a second layer containing a second water-soluble polymer. Each layer and the polymer will be described in detail below.

[0033] In one embodiment of the above dissolvable solid structure, the first layer may comprise a first water-soluble polymer and a component incompatible with at least one of the above components in the second layer, and the second layer may comprise a second water-soluble polymer, a high melting point fatty substance having a carbon chain length of C12 to C22 or a mixture thereof, the melting point of which is greater than 25° C., and a cationic surfactant.

[0034] In one embodiment, in the dissolvable solid structure of any of the above features, at least one of the first layer and the second layer may further comprise particles, preferably the second layer may further comprise particles.

[0035] In one embodiment, in the dissolvable solid structure of any of the above features, the first layer may have an aesthetic feature selected from the group consisting of printing, embossing, texture, coloring, and combinations thereof.

[0036] The dissolvable solid structure of the present invention is preferably a personal care product, more preferably a hair care product, even more preferably a rinse-off hair care product, and even more preferably a rinse-off hair care product containing a non-sulfate surfactant.

[0037] First Layer and First Water-Soluble Polymer The first layer comprises about 20% by weight to about 100% by weight of the first layer, preferably about 50% by weight to about 100% by weight, more preferably about 90% by weight to about 100% by weight, even more preferably about 95% by weight to about 100% by weight, and even more preferably about 99% by weight to about 100% by weight of the first water-soluble polymer.

[0038] The first water-soluble polymer can be a natural or synthetic polymer, provided that the first layer has a scaled tensile energy absorption at break (scaled TEA at break) value as described below. In other words, the first water-soluble polymer can be any polymer, so long as such polymer can be converted into a fibrous layer, and this layer can have sufficient strength to allow processing at a later stage of the manufacturing process, i.e., this layer exhibits sufficient strength to support a second layer during manufacturing, while allowing cutting of such layer or article.

[0039] Preferably, the first water-soluble polymer is (i) polyvinyl alcohol having a molecular weight of about 23,000 g / mol to about 45,000 g / mol, preferably about 25,000 g / mol to about 40,000 g / mol, more preferably about 26,000 g / mol to about 35,000 g / mol; (ii) a mixture of polyvinyl alcohols having an average molecular weight as a mixture of about 23,000 g / mol to about 45,000 g / mol, preferably about 25,000 g / mol to about 40,000 g / mol, and more preferably about 26,000 g / mol to about 35,000 g / mol; (iii) Thermally bound starch with or without plasticizer, having a molecular weight of about 1,000,000 g / mol to about 50,000,000 g / mol, preferably about 2,000,0000 g / mol to about 40,000,000 g / mol; (iv) polyvinylpyrrolidone, its copolymers, or mixtures thereof (e.g., PVP K60, available from Ashland, Inc., having a MW of about 400,000 g / mol); (v) polyvinyloxazoline, its copolymers, or mixtures thereof; (vi) poly(2-ethyl-2-oxazoline), its copolymers, or mixtures thereof; and (vii) is selected from the group consisting of polyvinyl caprolactam, its copolymers, or mixtures thereof.

[0040] Of these, the more preferred first water-soluble polymer is selected from (ii) a mixture of polyvinyl alcohols.

[0041] The first water-soluble polymer in the first layer can be the same as or different from the second polymer in the second layer.

[0042] As used herein, the term "water-soluble polymer" is broad enough to include both water-soluble and water-dispersible polymers, and is defined as a polymer with a water solubility measured at 25°C of at least about 0.1 grams per liter (g / L). In some embodiments, the polymer has a water solubility measured at 25°C of about 0.1 grams per liter (g / L) to about 500 grams per liter (g / L), which indicates the formation of a macroscopically isotropic or transparent, colored or colorless solution. The polymers for making these solids may be of synthetic or natural origin and may be modified by chemical reactions. They may or may not be film-forming. These polymers should be physiologically acceptable, i.e., the polymer should be compatible with the skin, mucous membranes, hair, and scalp.

[0043] The terms "water-soluble polymer" and "polymeric structurant" are used interchangeably herein. Furthermore, whenever the singular term "polymer" is mentioned, it should be understood that this term is broad enough to include one polymer or a mixture of two or more polymers. For example, when a mixture of polymers is used, the polymer solubility referred to herein will refer to the solubility of the mixture of polymers, not the individual solubility of each polymer.

[0044] Preferably, the first layer is substantially free of surfactants, especially when the first layer has an aesthetic feature selected from the group consisting of printing, embossing, texture, coloring, and combinations thereof. In the present invention, "the layer is substantially free of surfactants" means that the composition is free of surfactants, or, if the composition includes surfactants, the level of such surfactants is very low. In the present invention, the total level of such surfactants, if included, is preferably 1% or less by weight of the composition, more preferably 0.5% or less by weight, and more preferably 0.1% or less by weight. Most preferably, the total level of such surfactants is 0% by weight of the composition. Surfactant herein means any type of ionic surfactant, such as anionic, cationic, amphoteric, and zwitterionic surfactants. Surfactant herein also includes nonionic surfactants with an HLB greater than (excluding) 9.

[0045] The first layer may further comprise an oily component, such as oleic acid, having an HLB of 9 or less, preferably 3 or less. The oily component may be included in the first layer at a level of about 0.01% to about 2% by weight of the first layer, preferably about 0.1% to about 1% by weight.

[0046] Scaled fracture TEA It may be preferred that the first layer has a scaled tensile energy absorption at break (scaled TEA) of about 10 (g / cm) to about 185 (g / cm), preferably about 20 (g / cm) to about 180 (g / cm), and more preferably about 25 (g / cm) to about 175 (g / cm).

[0047] Scaled broken TEA is broken TEA scaled to a common basis weight, i.e., 50 gsm herein. Since broken TEA depends on the amount of material present in either the thickness or cross-sectional area, this allows for comparison of strength of different basis weight materials. The method for measuring broken TEA is given below.

[0048] Method for measuring broken TEA Sample Preparation: A steel rule die on a 12"x12" plywood base punches strips from the material. Equilibration: 73F and 50% RH for at least 15 minutes. Crosshead speed: 2 inches / minute Sample width: 1 inch Gauge Length: 1 inch Data Analysis: Break TEA (area under the curve at the break point as outlined in Break Stretch).

[0049] Second Layer and Second Water-Soluble Polymer The second layer comprises about 1% to about 50% by weight of the second layer of a second water-soluble polymer, preferably about 1% to about 20% by weight, more preferably about 1% to about 10% by weight, even more preferably about 2% to about 6% by weight, and even more preferably about 3% to about 5% by weight.

[0050] The second soluble polymer can be any polymer, preferably different from the first polymer in the first layer. The structuring agent has a weight average molecular weight of about 10,000 to about 6,000,000 g / mol. A structuring agent having a weight average molecular weight of about 3,000,000 g / mol to about 5,000,000 g / mol is included at a level of about 3% to about 6% by weight. Alternatively, a structuring agent having a weight average molecular weight of about 50,000 g / mol to about 100,000 g / mol can be included at a level of about 30% to about 50% by weight.

[0051] Preferably, the second water-soluble polymer is selected from the group consisting of polyvinylpyrrolidone, preferably polyvinylpyrrolidone copolymer, polydimethylacrylamide, preferably polydimethylacrylamide copolymer, poly(vinyloxazoline), preferably poly 2-ethyl-2-oxazoline, polyvinylcaprolactam copolymer, preferably polyvinylcaprolactam, and combinations thereof.

[0052] As used herein, "vinylpyrrolidone copolymer" (and when used in reference thereto, "copolymer") refers to a polymer of structure (I):

[0053] [ka]

[0054] In structure (I), n is an integer such that the polymeric structurant has a degree of polymerization such that it has the properties described herein. For clarity, the use of the term "copolymer" is intended to convey that vinylpyrrolidone monomers can be copolymerized with other monomers, such as, but not limited to, vinyl acetate, alkylated vinylpyrrolidone, vinyloxazoline, vinylcaprolactam, vinylvalerolactam, vinylimidazole, acrylic acid, methacrylate, acrylamide, methacrylamide, dimethacrylamide, alkylaminomethacrylate, and alkylaminomethacrylamide monomers.

[0055] For example, a suitable polymer for use is PVP K120 from Ashland Inc., which has a weight average molecular weight of about 3,500,000 g / mol, is soluble in oil and water, and allows fibers to form and collect on the belt. Further suitable polymers include copolymers of polyvinylpyrrolidone, such as Ganex®, or PVP / VA (weight average molecular weight of about 50,000 g / mol) copolymer from Ashland Inc., which also act as suitable structuring agents, but due to their low weight average molecular weight, higher levels are utilized to be effective. Further suitable polymers include poly(2-ethyl-2-oxazoline), polyvinylcaprolactam, and polydimethylacrylamide, and copolymers thereof.

[0056] Dispersants The second layer may further include a dispersant to increase wetting, hydration, and / or dispersion of the conditioner material. The dispersant may be included at a level of about 1% to about 30%, alternatively about 5% to about 15%, alternatively about 5% to about 10% by weight of the second layer. Surfactants from the non-ionic class of alkyl glucamides can improve wetting and hydration when added to solid conditioner formulations. Alkyl glucamide surfactants contain a hydrophobic tail of about 8 to 18 carbons and a non-ionic head group of glucamide. With respect to the glucamides, the presence of the amide and hydroxyl groups provides sufficient polarity to balance the hydrophobic carbon tail in a manner that allows solubility of the surfactant in the conditioner oil and also results in rapid dispersion of the conditioner ingredients upon exposure to water. Other similar dispersing agents include, but are not limited to, reverse alkyl glucamides, gluconamides, cocoamidopropyl betaine, alkyl glucosides, triethanolamine, cocamide MEA, and mixtures thereof.

[0057] Alkyl glucamide surfactants, especially when used in conjunction with polyvinylpyrrolidone, can provide hair styling benefits. Such benefits of alkyl glucamide surfactants can be seen regardless of the product form, i.e., from solid forms such as dissolvable solid structures, as well as from liquid forms.

[0058] Cationic Surfactants The second layer comprises a cationic surfactant which may be present at a level of from about 1% to about 60%, alternatively from about 10% to about 50%, alternatively from about 20% to about 40% by weight of the second layer.

[0059] The cationic surfactant useful herein can be one cationic surfactant or a mixture of two or more cationic surfactants.The cationic surfactant can be selected from, but is not limited to, the group consisting of mono-long alkyl quaternary ammonium salt, the combination of mono-long alkyl quaternary ammonium salt and di-long alkyl quaternary ammonium salt, mono-long alkyl amine, the combination of mono-long alkyl amine and di-long alkyl quaternary ammonium salt, and the combination of mono-long alkyl amine and mono-long alkyl quaternary ammonium salt, tertiary amine, and combinations thereof.

[0060] Mono long chain alkylamine Mono-long chain alkylamines useful herein are those having one long alkyl chain of 12 to 30 carbon atoms, alternatively 16 to 24 carbon atoms, alternatively 18 to 22 alkyl groups. Mono-long chain alkylamines useful herein also include mono-long chain alkyl amidoamines. Primary, secondary, and tertiary aliphatic amines are useful.

[0061] Tertiary amidoamines having an alkyl group of about 12 to about 22 carbons are suitable for use in the dissolvable solid structure. Exemplary tertiary amidoamines include stearamidopropyl dimethylamine, stearamidopropyl diethylamine, stearamidoethyl diethylamine, stearamidoethyl dimethylamine, palmitamidopropyl dimethylamine, palmitamidopropyl diethylamine, palmitamidoethyl diethylamine, palmitamidoethyl dimethylamine, behenamidopropyl dimethylamine, behenamidopropyl diethylamine, behenamidoethyl diethylamine, behenamidoethyl dimethylamine, arachidamidopropyl dimethylamine, arachidamidopropyl diethylamine, arachidamidoethyl diethylamine, arachidamidoethyl dimethylamine, diethylaminoethyl stearamide. Amines useful in the present invention are disclosed in U.S. Pat. No. 4,275,055 (Nachtigal et al.).

[0062] These amines may be used in combination with acids such as l-glutamic acid, lactic acid, hydrochloric acid, malic acid, succinic acid, acetic acid, fumaric acid, tartaric acid, citric acid, l-glutamic acid hydrochloride, maleic acid, and mixtures thereof, or l-glutamic acid, lactic acid, citric acid, etc., in a molar ratio of amine to acid of about 1:0.3 to about 1:2, or about 1:0.4 to about 1:1.

[0063] Mono long chain alkyl quaternary ammonium salt Mono long chain alkyl quaternized ammonium salts useful herein are those having one long alkyl chain having 12 to 30 carbon atoms, alternatively 16 to 24 carbon atoms, alternatively a C18-22 alkyl group. The remaining groups attached to the nitrogen are independently selected from alkyl groups of 1 to about 4 carbon atoms, or alkoxy, polyoxyalkylene, alkylamido, hydroxyalkyl, aryl, or alkylaryl groups having up to about 4 carbon atoms.

[0064] The mono-long chain alkyl quaternized ammonium salts useful herein have the formula (I):

[0065] [ka] In the formula, R 75 , R 76 , R 77 , and R 78 is selected from an alkyl group of 12 to 30 carbon atoms, or an aromatic group, an alkoxy group, a polyoxyalkylene group, an alkylamido group, a hydroxyalkyl group, an aryl group, or an alkylaryl group having up to about 30 carbon atoms; R 75 , R 76 , R 77 , and R 78 the remainder are independently selected from an alkyl group of 1 to about 4 carbon atoms, or an alkoxy group, a polyoxyalkylene group, an alkylamido group, a hydroxyalkyl group, an aryl group, or an alkylaryl group having up to about 4 carbon atoms; - is a salt-forming anion such as one selected from the groups halogen (e.g., chloride, bromide), acetate, citrate, lactate, glycolate, phosphate, nitrate, sulfonate, sulfate, alkylsulfate, and alkylsulfonate. In addition to carbon and hydrogen atoms, the alkyl groups can contain ether and / or ester linking groups, as well as other groups such as amino groups. Longer chain alkyl groups, e.g., those having about 12 carbon atoms or more, can be saturated or unsaturated. R 75 , R 76 , R 77 , and R 78 may be selected from alkyl groups of 12 to 30 carbon atoms, alternatively 16 to 24 carbon atoms, alternatively 18 to 22 carbon atoms, alternatively 22 carbon atoms; R 75 , R 76 , R 77 , and R 78The remainder of may be independently selected from CH3, C2H5, C2H4OH, and combinations thereof, and X may be selected from the group consisting of Cl, Br, CH3OSO3, C2H5OSO3, and combinations thereof.

[0066] Non-limiting examples of such mono-long chain alkyl quaternized ammonium salt cationic surfactants include behenyltrimethylammonium salts, stearyltrimethylammonium salts, cetyltrimethylammonium salts, and hydrogenated tallow alkyltrimethylammonium salts.

[0067] Di-long chain alkyl quaternary ammonium salt When used, the di-long chain alkyl quaternized ammonium salt may be combined with the mono-long chain alkyl quaternized ammonium salt and / or the mono-long chain alkyl amine salt in a weight ratio of 1:1 to 1:5, alternatively 1:1.2 to 1:5, alternatively 1:1.5 to 1:4, from the viewpoint of the stability of the rheological effect and the conditioning effect.

[0068] The di-long chain alkyl quaternized ammonium salts useful herein are those having two long alkyl chains of 12 to 30 carbon atoms, alternatively 16 to 24 carbon atoms, alternatively 18 to 22 carbon atoms. Such di-long chain alkyl quaternized ammonium salts useful herein have the formula (I):

[0069] [ka] In the formula, R 71 , R 72 , R 73 , and R 74 two of R are selected from aliphatic groups having 12 to 30 carbon atoms, alternatively 16 to 24 carbon atoms, alternatively 18 to 22 carbon atoms, or aromatic, alkoxy, polyoxyalkylene, alkylamido, hydroxyalkyl, aryl, or alkylaryl groups having up to about 30 carbon atoms; 71 , R 72 , R 73, and R 74 the remainder are independently selected from aliphatic groups of 1 to about 8 carbon atoms, alternatively 1 to 3 carbon atoms, or aromatic, alkoxy, polyoxyalkylene, alkylamido, hydroxyalkyl, aryl, or alkylaryl groups having up to about 8 carbon atoms; - R is a salt-forming anion selected from the group consisting of halides such as chloride and bromide, C1-C4 alkyl sulfates such as methosulfate and ethosulfate, and mixtures thereof. The aliphatic groups can contain, in addition to carbon and hydrogen atoms, ether linking groups, and other groups such as amino groups. Longer chain aliphatic groups, e.g., those having about 16 carbon atoms or more, can be saturated or unsaturated. R 71 , R 72 , R 73 , and R 74 two of R may be selected from alkyl groups of 12 to 30 carbon atoms, alternatively 16 to 24 carbon atoms, alternatively 18 to 22 carbon atoms; 71 , R 72 , R 73 , and R 74 the remainder are independently selected from CH3, C2H5, C2H4OH, CH2C6H5, and combinations thereof.

[0070] Suitable di-long chain alkyl cationic surfactants include, for example, dialkyl(14-18)dimethylammonium chloride, ditallow alkyl dimethylammonium chloride, dihydro-added tallow alkyl dimethylammonium chloride, distearyl dimethylammonium chloride, and dicetyl dimethylammonium chloride.

[0071] High melting point fatty compounds The second layer includes a high melting point fatty compound. The high melting point fatty compound may be present at a level of about 10% to about 85%, alternatively 20% to 70%, alternatively about 50% to about 70%, alternatively about 10% to about 20% by weight of the second layer. The fatty compound may be selected from the group consisting of, but is not limited to, fatty amphiphiles, fatty alcohols, fatty acids, fatty amides, fatty esters, and combinations thereof.

[0072] High melting point fatty compounds useful herein have a melting point of 25°C or more, alternatively 40°C or more, alternatively 45°C or more, alternatively 50°C or more, from the viewpoint of emulsion, especially gel matrix stability. Such melting points are up to about 90°C, alternatively up to about 80°C, alternatively up to about 70°C, alternatively up to about 65°C, from the viewpoint of easier preparation and easier emulsification. The high melting point fatty compounds can be used as a single compound or as a blend or mixture of at least two high melting point fatty compounds. When used as such a blend or mixture, the above melting point refers to the melting point of the blend or mixture.

[0073] The useful high melting point fatty compounds herein are selected from the group consisting of fatty alcohols, fatty acids, fatty alcohol derivatives, fatty acid derivatives, fatty amides, and mixtures thereof. Those skilled in the art will understand that the compounds disclosed in this section of the present specification may belong to more than one classification in some cases, for example, some fatty alcohol derivatives may also be classified as fatty acid derivatives. However, the classification given is not intended to limit the specific compound, but is made so for the convenience of classification and nomenclature. Furthermore, those skilled in the art will understand that depending on the number and position of double bonds and the length and position of branching, certain compounds with certain required carbon atoms may have melting points below the above. Such compounds with low melting points are not intended to be included in this section. Non-limiting examples of high melting point compounds can be found in the International Cosmetic Ingredient Dictionary, Fifth Edition, 1993, and the CTFA Cosmetic Ingredient Handbook, Second Edition, 1992.

[0074] Of the various high melting point fatty compounds, fatty alcohols may be used in the compositions described herein. The fatty alcohols useful herein are those having from about 14 to about 30 carbon atoms, alternatively from about 16 to about 22 carbon atoms. These fatty alcohols are saturated and may be straight or branched chain alcohols.

[0075] Suitable fatty alcohols include, but are not limited to, cetyl alcohol (having a melting point of about 56°C), stearyl alcohol (having a melting point of about 58-59°C), behenyl alcohol (having a melting point of about 71°C), and mixtures thereof. These compounds are known to have the above melting points. However, they often have lower melting points when supplied, because such supplied products are often mixtures of fatty alcohols with alkyl chain length distributions, where the predominant alkyl chains are cetyl, stearyl, or behenyl.

[0076] Generally, in the mixture, the weight ratio of cetyl alcohol to stearyl alcohol is from about 1:9 to 9:1, alternatively from about 1:4 to about 4:1, alternatively from about 1:2.3 to about 1.5:1.

[0077] When higher levels of total cationic surfactant and high melting point fatty compound are used, the mixture has a weight ratio of cetyl alcohol to stearyl alcohol of about 1:1 to about 4:1, alternatively about 1:1 to about 2:1, alternatively about 1.2:1 to about 2:1, in order to maintain acceptable consumer usage levels, which also provides better conditioning of damaged areas of the hair.

[0078] Plasticizer The first layer and / or the second layer optionally comprise from about 1% to about 25% plasticizer by weight of the layer, and in one embodiment from about 3% to about 20% plasticizer by weight of the layer, and in one embodiment from about 5% to about 15% plasticizer by weight of the layer.

[0079] When present in the structure, non-limiting examples of suitable plasticizers include polyols, copolyols, polycarboxylic acids, polyesters, and dimethicone copolyols.

[0080] Examples of useful polyols include, but are not limited to, monosaccharides, disaccharides, and oligosaccharides such as glycerin, diglycerin, propylene glycol, ethylene glycol, butylene glycol, pentylene glycol, cyclohexanedimethanol, hexanediol, polyethylene glycol (200-600), sugar alcohols such as sorbitol, mannitol, lactitol, isosorbide, glucamine, N-methylglucamine, and other mono- and polyhydric low molecular weight alcohols (e.g., C2-C8 alcohols), fructose, glucose, sucrose, maltose, lactose, and high fructose corn syrup solids, and ascorbic acid.

[0081] Examples of polycarboxylic acids include, but are not limited to, citric acid, maleic acid, succinic acid, polyacrylic acid, and polymaleic acid.

[0082] Examples of suitable polyesters include, but are not limited to, glycerol triacetate, acetylated monoglycerides, diethyl phthalate, triethyl citrate, tributyl citrate, acetyl triethyl citrate, acetyl tributyl citrate.

[0083] Examples of suitable dimethicone copolyols include, but are not limited to, PEG-12 dimethicone, PEG / PPG-18 / 18 dimethicone, and PPG-12 dimethicone.

[0084] Other suitable plasticizers include alkyl and aryl phthalates, naphthalates, lactates (e.g., sodium, ammonium, and potassium salts), Sorbeth-30, urea, lactic acid, pyrrolidone carboxylic acid (PCA), sodium hyaluronate or hyaluronic acid, soluble collagen, modified proteins, monosodium L-glutamate, alpha- and beta-hydroxyl acids such as glycolic acid, lactic acid, citric acid, maleic acid, and salicylic acid, polymeric plasticizers such as glyceryl polymethacrylate, polyquaterniums, proteins, and amino acids such as glutamic acid, aspartic acid, and lysine, hydrogenated starch hydrolysates, and other low molecular weight esters (e.g., C2-C 10 Plasticizers that may be used include, but are not limited to, esters of alcohols and acids, and any other water soluble plasticizers known to those skilled in the art of the food and plastics industries, and mixtures thereof.

[0085] EP 0283165(B1) discloses suitable plasticizers, including glycerol derivatives such as propoxylated glycerol.

[0086] Optional Ingredients The first layer and / or second layer may include other optional ingredients known or otherwise useful for use in compositions, provided that such optional materials are compatible with the selected essential materials described herein or do not otherwise unduly impair product performance.

[0087] Such optional ingredients are most typically ingredients approved for use in cosmetics and described in references such as the "CTFA Cosmetic Ingredient Handbook" (Second Edition, The Cosmetic, Toiletries, and Fragrance Association, Inc. 1992).

[0088] Further non-limiting examples of such optional ingredients include preservatives, fragrances or fragrances, colorants or dyes, conditioning agents, hair bleaches, thickeners, moisturizers, emollients, pharmaceutical actives, vitamins or nutrients, sunscreens, deodorants, sensates, botanical extracts, nutrients, astringents, cosmetic particles, absorbent particles, adhesive particles, hair fixatives, fibers, reactive agents, whitening agents, tanning agents, anti-dandruff agents, fragrances, stripping agents, acids, makeup bases, moisturizers, enzymes, suspending agents, pH adjusters, hair colorants, hair perm agents, pigment particles, acne inhibitors, antibacterial agents, sunscreens, tanning agents, exfoliating particles, hair thickeners or growth agents, insect repellents, shaving lotions, co-solvents or other additional solvents, and other similar materials. Further non-limiting examples of optional ingredients include encapsulated perfumes, such as with beta-cyclodetrin, polymeric microcapsules, starch encapsulated accords, and combinations thereof.

[0089] Suitable conditioning agents include high melting point fatty compounds, silicone conditioning agents, and cationic conditioning polymers. Suitable materials are discussed in U.S. Patent Application Publication Nos. 2008 / 0019935, 2008 / 0242584, and 2006 / 0217288.

[0090] Physical properties of the soluble solid structures In the case of fibrous structures, the structures contain a substantial amount of soluble fibers having an average diameter of less than about 150 micrometers, alternatively less than about 100 micrometers, alternatively less than about 10 micrometers, and alternatively less than about 1 micrometer, with a relative standard deviation of less than 100%, alternatively less than 80%, alternatively less than 60%, alternatively less than 50%, such as within the range of 10% to 50%. As used herein, a substantial amount means at least 10% of all soluble fibers, alternatively at least 25% of all soluble fibers, alternatively at least 50% of all soluble fibers, alternatively at least 75% of all soluble fibers. A substantial amount may be at least 99% of all soluble fibers. Alternatively, about 50% to about 100% of all soluble fibers may have an average diameter of less than about 10 micrometers. The soluble fibers produced by the methods of the present disclosure have a substantial amount of soluble fibers having an average diameter of less than about 1 micrometer, i.e., sub-micrometer fibers. In one embodiment, the dissolvable solid structure may have about 25% to about 100% of all soluble fibers having an average diameter less than about 1 micrometer, alternatively about 35% to about 100% of all soluble fibers having an average diameter less than about 1 micrometer, alternatively about 50% to about 100% of all soluble fibers having an average diameter less than about 1 micrometer, or alternatively about 75% to about 100% of all soluble fibers having an average diameter less than about 1 micrometer.

[0091] The percent porosity of the dissolvable solid structure is at least about 25%, alternatively in embodiments at least about 50%, alternatively at least about 60%, alternatively at least about 70%, alternatively at least about 80%. The porosity of the dissolvable solid structure is no more than about 99%, alternatively no more than about 98%, alternatively no more than about 95%, alternatively no more than about 90%. The porosity of the structure is determined according to the procedure set forth in the definition of "porosity" above.

[0092] Pores of various effective sizes can be accommodated, and the pore size distribution across the cross section of the structure can be symmetric or asymmetric.

[0093] The structure may be flexible and the distance to the maximum force value may be from about 6 mm to about 30 mm. The distance to the maximum force value is from about 7 mm to about 25 mm, alternatively from about 8 mm to about 20 mm, alternatively from about 9 mm to about 15 mm.

[0094] The structure may be characterized in one aspect by its specific surface area. 2 / g~approx.0.25m 2 / g, or about 0.035m 2 / g~approx.0.22m 2 / g, or about 0.04m 2 / g ~ approx. 0.19m 2 / g, and / or about 0.045 m 2 / g~approx.0.16m 2 The material may have a specific surface area of ​​100 / g.

[0095] The structure may be a flat flexible structure in the form of a pad, strip, or tape, having a thickness of about 0.5 mm to about 10 mm, alternatively about 1 mm to about 9 mm, alternatively about 2 mm to about 8 mm, alternatively about 3 mm to about 7 mm, as measured by the following method. The structure may be a sheet having a thickness of about 5 mm to about 6.5 mm. Alternatively, two or more sheets are combined to form a structure having a thickness of about 5 mm to about 10 mm.

[0096] The structure is approximately 200 g / m 2 ~ approx. 2,000g / m 2 , or about 400 g / m 2 ~Approx. 1,200g / m 2 , or about 600 g / m 2 ~Approx. 2,000g / m 2 , and / or about 700 g / m 2 ~Approx. 1,500g / m 2 The sheet may have a basis weight of 100 g.

[0097] The structure is approximately 0.08 g / cm 3 ~Approx. 0.40g / cm 3 , or about 0.08 g / cm 3 ~Approx. 0.38g / cm 3 , or about 0.10 g / cm 3 ~Approx. 0.25g / cm 3 , or about 0.12 g / cm 3 ~Approx. 0.20g / cm 3 The dry density of the powder may be 0.01 to 0.05.

[0098] Manufacturing method - fiber structure Non-limiting examples of methods for producing fiber elements, particularly for the first layer A fiber element, e.g., a filament, may be made as shown in Figures 1 and 2. As shown in Figures 1 and 2, a method 20 for making a fiber element 10, e.g., a filament, includes: a. providing a fiber element forming composition 22, such as from a tank 24; b. spinning the fiber element forming composition 22, such as through a spinning die 26, into one or more fiber elements 10, such as filaments.

[0099] The fiber element forming composition may be transported between the tank 24 and the spinning die 26 via suitable piping 28 with or without the use of a pump 30. In one embodiment, a pressurized tank 24 suitable for batch operation is filled with a fiber element forming composition 22 suitable for spinning. A pump 30 such as a Zenith® PEP II model having a capacity of 5.0 cubic centimeters per revolution (cc / rev) manufactured by the Zenith Pumps division of Colfax Corporation of Monroe, North Carolina, USA may be used to facilitate the transport of the fiber element forming composition 22 to the spinning die 26. The flow rate of the fiber element forming composition 22 from the pressurized tank 24 to the spinning die 26 may be controlled by adjusting the revolutions per minute (rpm) of the pump 30. A pipe 28 is used to connect the pressurized tank 24, the pump 30, and the spinning die 26 to transport the fiber element forming composition 22 from the tank 24 to the pump 30 and into the die 26 (as represented by the arrows).

[0100] As shown in FIGS. 1 and 2 , the spinning die 26 may include a plurality of fiber element forming cavities 32 including melt capillaries 34 surrounded by concentric attenuation fluid holes 36 through which a fluid, such as air, passes upon exiting the fiber element forming cavities 32 to facilitate attenuation of the fiber element forming composition 22 into fiber elements 10.

[0101] In one embodiment, the spinning die 26 shown in FIG. 2 has two or more rows of circular extrusion nozzles (fiber element forming holes 32) spaced apart from one another with a pitch P of about 0.060 inches. The nozzles have individual inner diameters of about 0.012 inches and individual outer diameters of about 0.032 inches. Each individual nozzle includes a melt capillary 34 surrounded by an annular, diverging, flared orifice (concentric attenuating fluid hole 36) for supplying attenuating air to each individual melt capillary 34. The fiber element forming composition 22 extruded through the nozzle is surrounded and attenuated by a generally cylindrical stream of moist air supplied through the orifice to produce fiber elements 10.

[0102] Attenuated air may be provided by heating compressed air from a supply with an electric resistance heater, such as heaters manufactured by Chromalox, Division of Emerson Electric (Pittsburgh, Pa., USA). A suitable amount of steam was added to saturate or nearly saturate the heated air at conditions in the electrically heated, thermostatically controlled delivery pipe. Condensate was removed in an electrically heated, thermostatically controlled separator.

[0103] The initial fiber elements are dried by a drying air stream having a temperature of about 149° C. (about 300° F.) to about 315° C. (about 600° F.) by an electrical resistance heater (not shown) and delivered through a drying nozzle and projected at an angle of about 90° relative to the general orientation of the initial fiber elements being spun. The dried fiber elements may be collected on a collection device, such as a belt or fabric, which in one embodiment can impart a pattern, e.g., a non-random repeating pattern, to the fiber structure formed as a result of collecting the fiber elements on the belt or fabric. A vacuum source may be added beneath the formation zone to aid in the collection of the fiber elements at the collection device. The spinning and collection of the fiber elements produces a fiber structure comprising intertwined fiber elements, e.g., filaments.

[0104] In one embodiment, any volatile solvent, such as water, present in fiber element forming composition 22 is removed, such as by drying, during the spinning process as fiber elements 10 are formed. In one embodiment, more than 30% by weight, and / or more than 40% by weight, and / or more than 50% by weight of the volatile solvent, such as water, of the fiber element forming composition is removed, such as by drying the fiber elements 10 produced, during the spinning process.

[0105] Non-Limiting Examples of Methods for Making Filament-Forming Compositions Particularly for the Second Layer The filament-forming composition may be made by any suitable process, so long as the filament-forming composition is suitable for making an article of the present invention.

[0106] In one embodiment, one or more active agents, e.g., hair conditioning active agents such as cationic surfactants and high melting point fatty compounds, are added to a metal beaker (in the absence of free water) and heated to a temperature sufficient to melt the active agents, e.g., 80° C. The active agents are melted and optionally stirred until they form a homogenous fluid.

[0107] After the active agent is melted, other ingredients, e.g., one or more filament-forming materials, such as one or more structuring agents, are added to the homogenous fluid of the active agent. When added, the other ingredients are stirred into the homogenous fluid of the active agent until the other ingredients are homogenously dispersed throughout the homogenous fluid of the active agent and / or homogenously dissolved within the homogenous fluid of the active agent. All this is done while maintaining the homogenous fluid of the active agent at a temperature of at least the melting point of the lowest melting point active agent, e.g., 80°C.

[0108] This filament forming composition can then be used to make fibrous elements, and / or fibrous structures, and / or articles of the present invention.

[0109] Non-limiting examples of methods for producing fiber elements, particularly for the second layer The fiber elements may be made by any suitable process. Non-limiting examples of suitable processes for making the fiber elements are described below.

[0110] As shown in Figures 3 and 4, the fiber elements can be made as follows: The fiber elements can be formed by small scale equipment, schematic diagrams of which are shown in Figures 3 and 4. A pressurized tank 139 suitable for batch operation is charged with a suitable filament-forming composition. A 5.0 cubic centimeters per revolution (cm3) pump manufactured by the Zenith Pump Division of Parker Hannifin Corporation (Sanford, NC, USA) is used. 3A pump 140, such as a Zenith® PEP II model having a capacity of 1000 rpm (1000 / rev) may be used to facilitate transport of the filament-forming composition to the spinning die 142 via pipe 141. The flow rate of the filament-forming composition from the pressurized tank 139 to the spinning die 142 may be controlled by adjusting the revolutions per minute (rpm) of the pump 140. The pipe 141 is used to connect the pressurized tank 139, the pump 140, and the spinning die 142.

[0111] The spinning die 142 shown in FIG. 3 has several rows of circular extrusion nozzles (fiber element forming holes 44) spaced apart from one another with a pitch P of about 0.060 inches. The nozzles have individual inner diameters of about 0.012 inches and individual outer diameters of about 0.032 inches. Each individual nozzle is surrounded by an annular, diverging, flared orifice (concentric attenuating fluid hole 148) for supplying attenuating air to each individual melt capillary 146. The filament-forming composition extruded through the nozzle is surrounded and attenuated by a generally cylindrical stream of moist air supplied through the orifice.

[0112] In one embodiment, as shown in FIGS. 3 and 4, a method for making fiber elements 110 includes: a. providing a filament-forming composition comprising one or more filament-forming materials, and optionally one or more active agents; b. spinning the filament-forming composition, such as via a spinning die 142, into one or more fiber elements, such as filaments 110, that include one or more filament-forming materials and, optionally, one or more active agents. The one or more active agents may be releasable from the fiber elements when exposed to intended use conditions.

[0113] As shown in FIG. 4 , the spinning die 142 may include a plurality of fiber element forming cavities 144 including melt capillaries 146 surrounded by concentric attenuation fluid cavities 148 through which a fluid, such as air, passes upon exiting the fiber element forming cavities 144 to facilitate attenuation of the filament forming composition into fiber elements, e.g., filaments 110.

[0114] Attenuated air may be provided by heating compressed air from a supply with an electric resistance heater, such as heaters manufactured by Chromalox, Division of Emerson Electric (Pittsburgh, Pa., USA). A suitable amount of steam is added to saturate or nearly saturate the heated air at conditions in an electrically heated, thermostatically controlled delivery pipe. Condensate is removed in an electrically heated, thermostatically controlled separator.

[0115] The embryonic fiber elements are quenched by a cooling air stream having a temperature of about 5° C. (about 41° F.) to about 40° C. (about 104° F.) delivered by a cooling air handler (not shown) through a cooling air duct and directed at an angle of about 90° relative to the general orientation of the embryonic fiber elements being extruded. The dried embryonic fiber elements are collected on a collection device, such as, for example, a movable foraminous belt or a patterned collection belt. A vacuum source may be added beneath the formation zone to aid in fiber collection.

[0116] Non-Limiting Examples of Methods for Making Articles 5, another embodiment of an article 220, e.g., a fibrous structure of the present disclosure, includes a first fibrous structure layer 222 including a plurality of fibrous elements, e.g., filaments 210, a second fibrous structure layer 224 including a plurality of fibrous elements, e.g., filaments 210, e.g., active agent-containing filaments, and a plurality of particles 226, e.g., active agent-containing particles, distributed, in this case randomly, in the x-, y-, and z-axes throughout the second fibrous structure layer 224. Alternatively, in another embodiment, the plurality of particles 226, e.g., active agent-containing particles, may be distributed within the second fibrous structure layer 224 in an irregular or non-random repeating pattern. As discussed above, a similar article including a two-ply fibrous structure includes a first fibrous structure ply 222 including a plurality of fibrous elements, e.g., filaments 210, a second fibrous structure ply 224 including a plurality of fibrous elements, e.g., filaments 210, e.g., active agent-containing filaments, and a plurality of particles 226, e.g., active agent-containing particles, distributed, in this case randomly, in the x-, y-, and z-axes throughout the second fibrous structure ply 224. Alternatively, in another embodiment, the plurality of particles 226, e.g., active agent-containing particles, may be distributed within the second fibrous structure ply 224 in an irregular or non-random repeating pattern.

[0117] In one embodiment, in a multi-ply article, one or more fibrous structure plies may be formed and / or deposited directly onto a pre-existing fibrous structure ply to form a multi-ply fibrous structure. Two or more pre-existing fibrous structure plies may be joined with one or more other pre-existing fibrous structure plies to form a multi-ply article of the invention, for example, via thermal bonding, gluing, embossing, perforating, rod insertion, rotary knife drilling, die punching, die punching, needle punching, knurling, pneumatic forming, hydroforming, laser cutting, tufting, and / or other mechanical joining processes.

[0118] How to use The dissolvable solid substrates described herein can be used to clean and / or treat hair, hair follicles, skin, teeth, and oral cavity. Methods for treating these consumer substrates may include a) applying an effective amount of the structure to the hands, b) wetting the structure with water to dissolve the solids, c) applying the dissolved material to the target consumer substrate, such as to clean or treat the target consumer substrate, and d) rinsing the diluted treatment composition from the consumer substrate. These steps can be repeated as many times as necessary to achieve the desired cleaning and / or treatment effect.

[0119] Useful methods for providing benefits to hair, hair follicles, skin, teeth, and / or oral cavity include applying a composition according to the first embodiment to those target consumer substrates requiring conditioning.

[0120] Alternatively, useful methods for regulating the condition of hair, hair follicles, skin, teeth, and oral cavity include applying one or more of the compositions described herein to those target consumer substrates in need of conditioning.

[0121] The amount of composition applied, frequency of application, and duration of use vary widely depending on the purpose of application, the level of components of a given composition, and the level of conditioning desired.For example, when the composition is applied to the whole body or hair treatment, the effective amount generally ranges from about 0.5 grams to about 10 grams, alternatively from about 1.0 grams to about 5 grams, and alternatively from about 1.5 grams to about 3 grams.

[0122] Product type and item Non-limiting examples of products utilizing the dissolvable solid structures include hand cleansing substrates, tooth cleaning or treatment substrates, oral substrates, hair cleansing or other hair treatment substrates, body cleansing substrates, shaving preparation substrates, personal care substrates containing medicinal or other skin care actives, moisturizing substrates, sunscreen substrates, long term skin benefit agent substrates (e.g., vitamin-containing substrates, alpha-hydroxy acid-containing substrates, etc.), deodorant substrates, fragrance-containing substrates, and the like.

[0123] Preferably, the dissolvable solid structure of the present invention is a personal care product, more preferably a hair care product, even more preferably a rinse-off hair care product, and even more preferably a rinse-off hair care product containing a non-sulfate surfactant.

[0124] Disclosed herein is an article of manufacture comprising one or more of the dissolvable solid structures described herein, and information directing the consumer to dissolve the structures and apply the dissolved mixture to hair, hair follicles, skin, teeth, or oral cavity to achieve a benefit on a target consumer substrate, a fast foaming foam, a fast rinsing foam, a clean rinsing foam, and combinations thereof. The information may be a printed matter attached directly or indirectly to the packaging containing the dissolvable solid structures or to the dissolvable solid structures themselves. Alternatively, the information may be an electronic or broadcast message associated with the article of manufacture. Alternatively, the information may describe at least one possible use, function, distinguishing feature, and / or characteristic of the article of manufacture.

[0125] Test Method Basis Weight Measurement Generally, the basis weight of a material or article (including a dissolvable solid structure) is measured by first cutting a sample to a known area using a die cutter or equivalent, then measuring and recording the weight of the sample on a top-loading balance with a minimum resolution of 0.01 g, and then finally calculating the basis weight as follows: Basis weight (g / m 2 ) = Weight of pad (g)

[0126]

number

[0127] The preferred pad sample size for determining basis weight is 10 cm 2 The soluble solid structure to be measured should be 10 cm or larger and cut with a precision die cutter having the desired shape. 2If less than 100%, then appropriate modifications can be made to the calculations to allow for a smaller sampling area to determine basis weight.

[0128] In this embodiment, 17.28 cm 2 The basis weight was calculated based on the total dissolvable solids structure having a known area of ​​1000 mm. Thus, the basis weight calculation is:

[0129]

number

[0130] Hand dissolution test method Materials required: Dissolvable solid structures to be tested: 3-5 dissolvable solid structures (final product samples) are tested and the average number of strokes for each individual dissolvable solid structure sample is calculated and recorded as the average hand dissolution value for the dissolvable solid structure. For this method, the entire consumer saleable dissolvable solid structure or consumer use dissolvable solid structure is tested. The entire consumer saleable dissolvable solid structure or consumer use dissolvable solid structure is measured over a 50 cm 2 If the installation area exceeds 50 cm 2 The dissolvable solid structure is cut to have a footprint of Nitrile gloves 10cc Syringe Plastic weighing boat (approximately 3" x 3") 100mL glass beaker Water (City of Cincinnati water or equivalent having the following characteristics: total hardness = 155 mg / L (as CaCO2), calcium content = 33.2 mg / L, magnesium content = 17.5 mg / L, phosphate content = 0.0462 mg / L) The water used has a hardness of 7 gpg and a temperature of 40°C + / - 5°C.

[0131] protocol: 1. Add 80 mL of water to a glass beaker. Add 300-500 mL of water to a glass beaker. 2. Heat the water in a beaker until the water is at a temperature of 40°C + / - 5°C. 3. Transfer 10 mL of water from the beaker to the weigh boat via syringe. 4. Within 10 seconds of transferring the water to the weigh boat, place the dissolvable solid structure sample in the palm of your gloved hand (your non-dominant hand cupped to hold the dissolvable solid structure sample). 5. Using your dominant hand, quickly add the water from the weigh boat to the soluble solid structure sample and immediately wet for 5-10 seconds. 6. Using your non-dominant hand (also gloved), rub together in two quick circular strokes. 7. After two strokes, visually inspect the dissolving solid structure sample in the hand. If the dissolving solid structure sample is completely dissolved, record the number of strokes = 2 dissolving strokes. If not completely dissolved, rub the remaining dissolving solid structure sample with two more circular strokes (total of four) and observe the degree of dissolution. If the dissolving solid structure sample does not contain solid pieces after two additional strokes, record the number of strokes = 4 dissolving strokes. If the dissolving solid structure sample still contains solid pieces of the dissolving solid structure sample that have not dissolved after a total of four strokes, continue to rub the remaining dissolving solid structure sample with two more circular strokes until the dissolving solid structure sample is completely dissolved or the total strokes reach 30, whichever comes first, and check whether any remaining solid pieces of the dissolving solid structure sample remain after each additional two strokes. Record the total number of strokes. Record 30 dissolving strokes even if solid dissolving solid structure sample pieces remain after the maximum of 30 strokes. 8. Repeat this process for each of the four more dissolvable solid structure samples. 9. Calculate the arithmetic mean of the recorded dissolution stroke values ​​for the five individual dissolving solid structure samples and record as the average hand dissolution value for the dissolving solid structure. The average hand dissolution value is reported to the nearest single dissolution stroke unit.

[0132] Fiber structure - fiber diameter For fibrous structures, the diameter of the soluble fibers in the web sample is determined by using a Scanning Electron Microscope (SEM) or optical microscope and image analysis software. A magnification of 200-10,000x is chosen so that the fibers are suitably magnified for measurement. When using an SEM, the sample is sputtered with gold or palladium compounds to avoid charging and vibration of the fibers in the electron beam. A manual procedure is used to determine the fiber diameter from the image (on a monitor screen) taken with the SEM or optical microscope. Using the mouse and cursor tool, locate the edge of a randomly selected fiber and then measure across its width (i.e. perpendicular to the fiber direction at that time) to the other edge of the fiber. A scaled and calibrated image analysis tool provides scaling to obtain an actual reading in micrometers (μm). Using the SEM or optical microscope, a few fibers are randomly selected across the web sample. At least two specimens are cut from the web (or the web in the product) and tested in this manner. For statistical analysis, a total of at least 100 such measurements are performed and all data is then recorded. The recorded data is used to calculate the mean (average) fiber diameter, the standard deviation of the fiber diameter, and the median fiber diameter. Another useful statistic is the calculation of the amount of fiber population below a particular upper limit. To determine this statistic, the software is programmed to count how many of the fiber diameter results are below the upper limit, and this count (divided by the total number of data and multiplied by 100%) is reported in percent as the percent below the upper limit, e.g., percent below 1 micrometer diameter, or % sub-micrometer. We define the measured diameter (in micrometers) of each individual circular fiber as d i This is expressed as:

[0133] In cases where the fibers have a non-circular cross section, the fiber diameter measurement is determined as and equal to the hydraulic diameter, which is the cross-sectional area of ​​the fiber multiplied by four divided by the perimeter of the cross section of the fiber (circumference in the case of hollow fibers). The number average diameter, or mean diameter, is d num It is calculated as:

[0134]

number

[0135] combination 1. A dissolvable solid structure comprising: a. a first layer comprising, by weight of the first layer, about 20% to about 100% by weight of a first water-soluble polymer of the first layer, preferably about 50% to about 100% by weight, more preferably about 90% to about 100% by weight, even more preferably about 95% to about 100% by weight, and even more preferably about 99% to about 100% by weight; b. A dissolvable solid structure comprising a second layer comprising: about 1% to about 50% by weight of the second layer, preferably about 1% to about 20% by weight, more preferably about 1% to about 10% by weight, still more preferably about 2% to about 6% by weight, and even more preferably about 3% to about 5% by weight of a second water-soluble polymer; a high melting point fatty substance having a carbon chain length of C12 to C22 or a mixture thereof, the melting point of which is greater than 25°C; and a cationic surfactant. 2. The dissolvable solid structure according to Feature 1, wherein the first layer has a scaled tensile energy absorption at break (scaled TEA at break) of about 10 (g / cm) to about 185 (g / cm), preferably about 20 (g / cm) to about 180 (g / cm), and more preferably about 25 (g / cm) to about 175 (g / cm). 3. The first water-soluble polymer is (i) polyvinyl alcohol having a molecular weight of about 23,000 g / mol to about 45,000 g / mol, preferably about 25,000 g / mol to about 40,000 g / mol, more preferably about 26,000 g / mol to about 35,000 g / mol; (ii) a mixture of polyvinyl alcohols having an average molecular weight as a mixture of about 23,000 g / mol to about 45,000 g / mol, preferably about 25,000 g / mol to about 40,000 g / mol, and more preferably about 26,000 g / mol to about 35,000 g / mol; (iii) Thermally bound starch with or without plasticizer, having a molecular weight of about 1,000,000 g / mol to about 50,000,000 g / mol, preferably about 2,000,0000 g / mol to about 40,000,000 g / mol; (iv) polyvinylpyrrolidone, its copolymers, or mixtures thereof; (v) polyvinyloxazoline, its copolymers, or mixtures thereof; (vi) poly(2-ethyl-2-oxazoline), its copolymers, or mixtures thereof; and (vii) The dissolvable solid structure according to any one of claims 1 to 2, wherein the dissolvable solid structure is selected from the group consisting of polyvinyl caprolactam, its copolymers, or mixtures thereof. 4. The dissolvable solid structure according to any one of Features 1 to 3, wherein the first water-soluble polymer is selected from a mixture of (ii) polyvinyl alcohols. 5. The dissolvable solid structure according to any one of Features 1 to 4, wherein the second water-soluble polymer is selected from the group consisting of polyvinylpyrrolidone, preferably polyvinylpyrrolidone copolymer, polydimethylacrylamide, preferably polydimethylacrylamide copolymer, polyvinyloxazoline, preferably poly 2-ethyl-2-oxazoline, polyvinylcaprolactam copolymer, preferably polyvinylcaprolactam, and combinations thereof. 6. the first layer comprises a first water-soluble polymer and a component that is incompatible with at least one of the components in the second layer; 6. The dissolvable solid structure according to any one of Features 1 to 5, wherein the second layer comprises a second water-soluble polymer, a high melting point fatty substance having a carbon chain length of C12 to C22 or a mixture thereof, the melting point of which is greater than 25° C., and a cationic surfactant. 7. The dissolvable solid structure according to any one of features 1 to 6, wherein the first layer has an aesthetic feature selected from the group consisting of printing, embossing, texture, coloring, and combinations thereof. 8. The dissolvable solid structure according to any one of Features 1 to 7, wherein the first layer is substantially free of a surfactant. 9. The dissolvable solid structure according to any one of Features 1 to 8, wherein at least one of the first layer and the second layer has particles, and preferably the second layer has particles. 10. The dissolvable solid structure according to any one of Features 1 to 9, wherein the dissolvable solid structure dissolves in less than 30 strokes by hand dissolving, preferably, the dissolvable solid structure dissolves in less than 20 strokes by hand dissolving, and even more preferably, the dissolvable solid structure dissolves in less than 15 strokes by hand dissolving. 11. The dissolvable solid structure according to any one of Features 1 to 10, wherein the dissolvable solid structure is a personal care product, preferably a hair care product, more preferably a rinse-off hair care product, and more preferably a rinse-off hair care product containing a non-sulfate surfactant.

[0136] Non-limiting examples The compositions shown in the following examples illustrate specific embodiments of the compositions, but are not intended to be limiting. Other modifications may be made by those skilled in the art without departing from the spirit and scope of the present invention. These illustrated embodiments of the compositions described herein provide enhanced conditioning benefits to hair.

[0137] Unless otherwise noted, all exemplified amounts are listed as weight percent and exclude minor materials such as diluents, preservatives, color solutions, imaging ingredients, botanicals, etc. All percentages are by weight unless otherwise indicated.

[0138] [Table 1] 1. Kurraray Selvol 403 2. Kurraray Selvol 420h 3. Selvol 505 made by Kurraray 4. Kurraray Selvol 205

[0139] [Table 2]

[0140] [Table 3]

[0141] [Table 4]

[0142] [Table 5]

[0143] The dissolvable solid structures of D-Example 1 to D-Example 6 are examples of the present invention using first layer examples F-Example 1 to F-Example 5 and some of the second layer examples such as S-Example 1. These examples of the present invention provide improved flexibility in the composition, in particular allowing the content of polymer to be reduced in at least one of the layers while maintaining a certain structural strength during manufacture and ease of cutting during and after manufacture.

[0144] When Comparative Example 1 was used for the first layer, the dissolvable solid structure was unable to maintain the desired sheet shape during production.When Comparative Example 2 was used for the first layer, the dissolvable solid structure was difficult to cut during and after production.

[0145] Dimensions and values ​​disclosed herein are not to be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."

[0146] All documents cited herein, including cross-referenced documents or related patents or applications, are incorporated herein by reference in their entirety, unless expressly excluded or otherwise limited. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest, or disclose any such invention, either alone or in combination with any other reference or references. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.

[0147] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.

Claims

1. A dissolvable solid structure comprising: a. a first layer, the first layer comprising, by weight of the first layer, about 20% to about 100%, preferably about 50% to about 100%, more preferably about 90% to about 100%, still more preferably about 95% to about 100%, and even more preferably about 99% to about 100% of a first water soluble polymer; b. a second layer comprising: about 1% to about 50%, preferably about 1% to about 20%, more preferably about 1% to about 10%, still more preferably about 2% to about 6%, and even more preferably about 3% to about 5% by weight of said second layer of a second water soluble polymer; a high melting point fatty material having a carbon chain length of C12-C22 or mixtures thereof, the melting point being greater than 25° C.; and a cationic surfactant; A dissolvable solid structure comprising:

2. The dissolvable solid structure of claim 1, wherein the first layer has a scaled tensile energy absorption at break (scaled TEA at break) of about 10 (g / cm) to about 185 (g / cm), preferably about 20 (g / cm) to about 180 (g / cm), more preferably about 25 (g / cm) to about 175 (g / cm).

3. The first water-soluble polymer is (i) polyvinyl alcohol having a molecular weight of about 23,000 g / mol to about 45,000 g / mol, preferably about 25,000 g / mol to about 40,000 g / mol, more preferably about 26,000 g / mol to about 35,000 g / mol; (ii) a mixture of polyvinyl alcohols, said mixture having an average molecular weight as a mixture of about 23,000 g / mol to about 45,000 g / mol, preferably about 25,000 g / mol to about 40,000 g / mol, more preferably about 26,000 g / mol to about 35,000 g / mol; (iii) Thermally bound starch with or without plasticizer, the molecular weight being from about 1,000,000 g / mol to about 50,000,000 g / mol, preferably from about 2,000,0000 g / mol to about 40,000,000 g / mol; (iv) polyvinylpyrrolidone, its copolymers, or mixtures thereof; (v) polyvinyloxazoline, its copolymers, or mixtures thereof; (vi) poly 2-ethyl-2 oxazoline, its copolymers, or mixtures thereof, and (vii) Polyvinyl caprolactam, its copolymers, or mixtures thereof. The dissolvable solid structure according to claim 1 or 2, selected from the group consisting of:

4. The dissolvable solid structure according to any one of claims 1 to 3, wherein the first water-soluble polymer is selected from the mixture of (ii) polyvinyl alcohol.

5. The dissolvable solid structure according to any one of claims 1 to 4, wherein the second water-soluble polymer is selected from the group consisting of polyvinylpyrrolidone, preferably polyvinylpyrrolidone copolymer, polydimethylacrylamide, preferably polydimethylacrylamide copolymer, polyvinyloxazoline, preferably poly 2-ethyl-2-oxazoline, polyvinylcaprolactam copolymer, preferably polyvinylcaprolactam, and combinations thereof.

6. the first layer comprises the first water-soluble polymer and a component that is incompatible with at least one of the components in the second layer; the second layer comprises the second water-soluble polymer, a high melting point fatty material having a carbon chain length of C12 to C22 or a mixture thereof, the melting point of which is greater than 25° C., and a cationic surfactant; The dissolvable solid structure according to any one of claims 1 to 5.

7. The dissolvable solid structure of any one of claims 1 to 6, wherein the first layer has an aesthetic feature selected from the group consisting of printing, embossing, texture, coloring, and combinations thereof.

8. The dissolvable solid structure according to any one of claims 1 to 7, wherein the first layer is substantially free of a surfactant.

9. The dissolvable solid structure according to any one of claims 1 to 8, wherein at least one of the first layer and the second layer comprises particles, preferably the second layer comprises the particles.

10. The dissolvable solid structure according to any one of claims 1 to 9, wherein the dissolvable solid structure dissolves in less than 30 strokes by hand dissolving method, preferably the dissolvable solid structure dissolves in less than 20 strokes by hand dissolving method, and even more preferably the dissolvable solid structure dissolves in less than 15 strokes by hand dissolving method.

Citation Information

Patent Citations

  • Compositions in the form of dissolvable solid structures containing expandable agglomerated particles

    JP2020506222A

  • Composition in the form of a dissolvable solid structure

    JP2020506893A

  • Conditioning hair care composition in the form of a dissolvable solid structure

    JP2020519616A

  • Conditioning hair compositions in the form of dissolvable solid structures

    US20190350819A1